2008
DOI: 10.1159/000137287
|View full text |Cite
|
Sign up to set email alerts
|

Early Bone Mineral Density Loss after Renal Transplantation and Pre-Transplant PTH: A Prospective Study

Abstract: Background: Post-transplant osteopathy is a known complication of kidney transplantation (KTx). The aim of this study was to assess bone mineral density (BMD) in a large cohort of patients with treatment depending on pre-transplant pa-rathormone (PTH) and baseline BMD. Patients and Methods: 347 consecutive KTx recipients (222 M, 125 F) finished all follow-up measurements of BMD at lumbar spine, femur and radius using DEXA Lunar (at baseline and at 6 and 18 months). Results: Bone loss with a T-score below –2.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Another important complication for patients with tertiary HPT is bone disease. The rate of osteoporosis is high in patients with a renal transplant, and tertiary HPT is associated with an increased risk of osteoporosis, and a major risk for fractures. Small trials have suggested that parathyroidectomy increases bone mineral density, in contrast to cinacalcet.…”
Section: Discussionmentioning
confidence: 99%
“…Another important complication for patients with tertiary HPT is bone disease. The rate of osteoporosis is high in patients with a renal transplant, and tertiary HPT is associated with an increased risk of osteoporosis, and a major risk for fractures. Small trials have suggested that parathyroidectomy increases bone mineral density, in contrast to cinacalcet.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have yielded conflicting data on the significance of pretransplant PTH levels as a predictor of posttransplant BMD loss: both high (20,(27)(28)(29) and low (15) pretransplant PTH levels have been correlated with BMD loss. Similar to FGF-23, pretransplant PTH levels are directly associated with post-transplant levels (7).…”
Section: Discussionmentioning
confidence: 99%
“…99 The disturbed bone mineralization observed in renal transplant recipients might be in part the result of post-transplantation hypophosphataemia and/or dysregulated FGF-23, independent of serum phosphate. Sustained or re-developed hyperparathyroidism after kidney transplantation might also be associated with bone alterations, although data are conflicting as to whether high pre-transplantation PTH levels can 103,104 or can not 105 predict the loss of BMD, and as previously discussed, low levels of PTH following transplantation are associated with a lower BMD. 98 Persistent hyperparathyroidism after kidney transplantation is associated with hypercalcaemia and hypophosphataemia, which may be effectively corrected with cinacalcet-a calcimimetic.…”
Section: Kidney Transplantationmentioning
confidence: 99%